Processing the method: Linking Deweyan logic and design-in-research. (September 2020) - Dixon, Brian; French, Tara
Abstract : This paper explores the relationship between design logic and reasoning and the methodological and epistemological positioning of design-based knowledge production. Examining the relevant literature, we propose that the naturalistic logic of the American pragmatist philosopher John Dewey offers a potentially useful contextualisation of how logic, reasoning, method and, ultimately, knowledge can be understood as arising from, and be responsive to, context. This is considered in relation to the long-term delivery of a design research programme—termed Experience Labs—which was seen to undergo a gradual methodological shift in response to contextual concerns. It is our core argument that Dewey's logic can function as a valuable theoretical device, mediating between design and the necessity of methodological and epistemological explication in research. Highlights: Logic of design literature suggests an emphasis on situatedness and recursivity. Design practice in research literature suggests an emphasis on situatedness and recursivity. John Dewey's logic supports the consideration of situatedness and recursivity in logic. Deweyan logic supports a post-rationalization of the evolution of a design research approach. Deweyan logic provides an epistemological rationale for inclusion of design practice in research.